KAJIAN PENDEKATAN MULTISENSORI PADA DESAIN JAWA TIMUR PARK 1 - Jihan Santya Maulida; Syaifuddin Zuhri (Jurnal Arsitektur ARCADE, 2025)
Abstract: Nowadays, educational tourism is gaining popularity as an alternative learning method outside traditional classrooms. Through recreational facilities with educational value, visitors are encouraged to learn while engaging in play. One notable destination is Jawa Timur Park 1, located in Batu, Malang. This park combines amusement rides with interactive science and cultural education exhibits, making it a unique educational tourism attraction. A major challenge for educational tourism is to provide a comprehensive and meaningful learning experience. The multisensory approach is considered an effective strategy to overcome this challenge. By integrating visual, auditory, kinesthetic, and other sensory elements, this approach aims to stimulate all senses of the visitors, thereby enhancing their understanding, engagement, and enjoyment of the learning process. This study uses a qualitative descriptive method to analyze how the multisensory approach is applied in Jawa Timur Park 1, based on the principles outlined in Peter Zumthor’s theory. The analysis identifies that the park successfully incorporates key multisensory elements, including spatial experience (the body of architecture), material coherence, lighting, visual engagement, soundscapes, and tactile experiences. Although not all elements are applied equally across every attraction, Jawa Timur Park 1 demonstrates how multisensory architecture can enrich educational tourism and improve visitor satisfaction. Keyword: Jawa Timur Park 1, Educational Tourism, Multisensory Approach. Abstrak: Pariwisata edukatif kini semakin menjadi sorotan karena mampu menghadirkan proses pembelajaran di luar sekolah melalui rekreasi yang bersifat edukatif. Pengunjung diajak bermain sambil belajar, seperti yang ditawarkan Jawa Timur Park 1 Batu, Malang. Tempat ini menggabungkan taman bermain dengan wahana edukasi budaya dan sains secara interaktif. Namun, pariwisata edukatif menghadapi tantangan dalam memberikan pengalaman belajar yang menyeluruh dan efektif. Pendekatan multisensori dinilai mampu mengatasi tantangan tersebut dengan mengintegrasikan elemen visual, auditif, kinestetik, dan sensorik lainnya. Pendekatan ini merangsang seluruh panca indra, sehingga meningkatkan pemahaman, keterlibatan, dan daya tarik pengalaman belajar. Penelitian ini menggunakan metode kualitatif dan analisis deskriptif dengan menguraikan prinsip-prinsip pendekatan multisensori menurut teori Peter Zumthor. Tujuannya adalah memberikan landasan ilmiah tentang bagaimana pariwisata edukatif dapat dikatakan responsif dan menciptakan pengalaman wisata yang berkesan. Studi kasus dilakukan pada Jawa Timur Park 1. Hasil analisis menunjukkan bahwa bangunan tersebut telah memenuhi beberapa parameter multisensori, seperti body of architecture, material compatibility, lighting, visual, auditory, dan haptic experience. Meskipun tidak semua aspek diterapkan secara menyeluruh, penerapan pendekatan ini memberikan kontribusi terhadap kualitas pengalaman pengunjung. Kata Kunci: Jawa Timur Park 1, Wisata Edukasi, Pendekatan Multisensori.